Public policies to reduce inappropriate tropical deforestation - Kaimowitz, D.; Byron, R.N.; Sunderlin, William D. (World Bank, 1998)
This paper explains the ways in which, and the extent to which, public policy measures might be used to reduce inappropriate tropical deforestation.Inappropriate deforestation is a signifanct problem: 1. deforestation generally causes negative externalities that generate cost to society not reflected in exixting prices and has long term consequences that individual producers rarely consider. 2. The relativie importance of the negative externalities tends to grow over time if an increasing proportion of deforestation occurs in areas that have only marginal value for agriculture but that sequester large amount of carbon, have fragile soils, or are high in biodiversity. The process of deforestation must be analysed at two levels: agents and causes. How certain causes can be manipulated to influence the behaviour of agents, so as to lessen the rate of inappropriate deforestation is discussed.